GSK-3 as a Target for Lithium-Induced Neuroprotection Against Excitotoxicity in Neuronal Cultures and Animal Models of Ischemic Stroke - Chuang, De-Maw; Wang, Zhifei; Chiu, Chi-Tso (Frontiers in Molecular Neuroscience, 2011)
The mood stabilizer lithium inhibits glycogen synthase kinase-3 (GSK-3) directly or indirectly by enhancing serine phosphorylation of both alpha and beta isoforms. Lithium robustly protected primary brain neurons from glutamate-induced excitotoxicity; these actions were mimicked by other GSK-3 inhibitors or silencing/inhibiting GSK-3alpha and/or beta isoforms. Lithium rapidly activated Akt to enhance GSK-3 serine phosphorylation and to block glutamate-induced Akt inactivation. Lithium also upregulated Bcl-2 and suppressed glutamate-induced p53 and Bax. Induction of BDNF was required for lithium’s neuroprotection to occur. BDNF promoter IV was activated by GSK-3 inhibition using lithium or other drugs, or through gene silencing/inactivation of either isoform. Further, lithium’s neuroprotective effects were associated with inhibition of NMDA receptor-mediated calcium influx and downstream signaling. In rodent ischemic models, post-insult treatment with lithium decreased infarct volume, ameliorated neurological deficits and improved functional recovery. Upregulation of heat shock protein 70 (HSP70) and Bcl-2 as well as downregulation of p53 likely contributed to lithium’s protective effects. Delayed treatment with lithium improved functional MRI responses, which was accompanied by enhanced angiogenesis. Two GSK-3-regulated pro-angiogenic factors, matrix metalloproteinase-9 (MMP-9) and vascular endothelial growth factor were induced by lithium. Finally, lithium promoted migration of mesenchymal stem cells (MSCs) by upregulation of MMP-9 through GSK-3beta inhibition. Notably, transplantation of lithium-primed MSCs into ischemic rats enhanced MSC migration to the injured brain regions and improved the neurological performance. Several other GSK-3 inhibitors have also been reported to be beneficial in rodent ischemic models. Together, GSK-3 inhibition is a rational strategy to combat ischemic stroke and other excitotoxicity-related brain disorders.